2021
DOI: 10.3390/app11052444
|View full text |Cite
|
Sign up to set email alerts
|

The Alterations in CD14 Expression in Periodontitis: A Systematic Review

Abstract: Objective: Cluster of differentiation (CD14) is an important protein involved in activating toll-like receptors by bacterial components. It exists as either a transmembrane or soluble protein, called mCD14 or sCD14, respectively. Several studies show that CD14 regulates the inflammatory response to periodontal pathogens, and its expression is altered in periodontitis, an inflammatory disease of tooth-supporting tissues. It is the intent of this review to investigate the levels of expression of mCD14 and sCD14 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 64 publications
(156 reference statements)
0
5
0
Order By: Relevance
“…Proteins that have low or no expression in saliva or salivary glands were also excluded from the validation list. The final shortlisted hits, namely, peroxiredoxin‐4 (PRX‐IV), legumain, SIL1 nucleotide exchange factor (SIL1), and cellular repressor of E1A‐stimulated genes (CREG1), were chosen based on novelty, 27–41 and the absence of association with other oral diseases 42–47 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Proteins that have low or no expression in saliva or salivary glands were also excluded from the validation list. The final shortlisted hits, namely, peroxiredoxin‐4 (PRX‐IV), legumain, SIL1 nucleotide exchange factor (SIL1), and cellular repressor of E1A‐stimulated genes (CREG1), were chosen based on novelty, 27–41 and the absence of association with other oral diseases 42–47 …”
Section: Resultsmentioning
confidence: 99%
“…The final shortlisted hits, namely, peroxiredoxin-4 (PRX-IV), legumain, SIL1 nucleotide exchange factor (SIL1), and cellular repressor of E1A-stimulated genes (CREG1), were chosen based on novelty, [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] and the absence of association with other oral diseases. [42][43][44][45][46][47] 2.2 | Salivary PRX-IV and legumain are significantly upregulated in HFMD case samples from Singapore Dot blot validation assay was performed using saliva samples from HFMD-diagnosed patients and healthy volunteers in Singapore to assess the sensitivity and specificity of the respective biomarker(s). A total of 28 HFMD cases and 43 healthy saliva samples were used for validation.…”
Section: Nineteen Salivary Proteins Were Significantly Upregulated In...mentioning
confidence: 99%
“…This change in the expression levels might be related to the presence of pathogenic gram-negative anaerobic microorganisms of periodontal diseases in human milk such as Porphyromonas gingivalis [ 48 ]. CD14 biomarker expressed on PMNs acts as a receptor for the LPS of gram-negative bacteria and studies reported higher expression levels of CD14 on oPMNs of patients with periodontitis compared to healthy individuals [ 49 ]. Since the pathogenicity of gram-negative anaerobic bacteria of periodontal diseases lie in its endotoxins including LPS [ 49 ], therefore it can be hypothesized that the higher expression levels of CD14 on hmPMNs of mothers with moderate to severe OIL might be related to the presence of these pathogenic bacteria in their human milk.…”
Section: Discussionmentioning
confidence: 99%
“…CD14 biomarker expressed on PMNs acts as a receptor for the LPS of gram-negative bacteria and studies reported higher expression levels of CD14 on oPMNs of patients with periodontitis compared to healthy individuals [ 49 ]. Since the pathogenicity of gram-negative anaerobic bacteria of periodontal diseases lie in its endotoxins including LPS [ 49 ], therefore it can be hypothesized that the higher expression levels of CD14 on hmPMNs of mothers with moderate to severe OIL might be related to the presence of these pathogenic bacteria in their human milk. Furthermore, studies have shown that the virulence factors of pathogenic bacteria can interfere with the neutrophils’ bactericidal activities, chemotaxis, and inhibition of neutrophil phagocytosis, where recent studies have shown that the upregulation of CD64 biomarker was inhibited when exposed to pathogenic oral bacteria, as opposed to its upregulation in case of commensal bacteria [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…These cells may be epithelium, fibroblast and so on. Therefore, it should be recognized that all forms of CD14 function as a receptor for byproducts of bacterial cell wall [32].…”
Section: Role Of Monocytes In Pathogenesis Of Periodontitismentioning
confidence: 99%